1993
DOI: 10.1002/1097-0142(19930115)71:2<430::aid-cncr2820710225>3.0.co;2-s
|View full text |Cite
|
Sign up to set email alerts
|

The management of ovarian carcinoma is improved by the use of cancer-associated serum antigen and CA 125 assays

Abstract: Background. The new tumor‐associated mucin assay, cancer‐associated serum antigen (CASA), was assessed with the CA 125 assay for use in the management of patients with epithelial ovarian cancer. Methods. CASA and CA 125 were assessed retrospectively for use in (1) monitoring 28 patients with Stage 3 or 4 ovarian carcinoma during therapy, (2) predicting the outcome of 41 second‐look laparotomies (SLL), and (3) predicting the survival outcome by measuring these levels after surgery but before chemotherapy in 65 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

1993
1993
2008
2008

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…In first-line treatment, the clinical course was accurately reflected in 65% of patients (19) , and the sensitivity of CASA to depict residual tumor at time of a second-look diagnostic operation ranged between 22% and 32% (14,16) . Furthermore, the prognostic value of CASA in primary clinical setting has been extensively studied and CASA level has been found to be a reliable prognostic factor for survival (13)(14)(15)(16)(17)(18) . This is the first report that evaluates the CASA level as a prognostic factor for survival in patients with recurrent ovarian cancer.…”
Section: Discussionmentioning
confidence: 99%
“…In first-line treatment, the clinical course was accurately reflected in 65% of patients (19) , and the sensitivity of CASA to depict residual tumor at time of a second-look diagnostic operation ranged between 22% and 32% (14,16) . Furthermore, the prognostic value of CASA in primary clinical setting has been extensively studied and CASA level has been found to be a reliable prognostic factor for survival (13)(14)(15)(16)(17)(18) . This is the first report that evaluates the CASA level as a prognostic factor for survival in patients with recurrent ovarian cancer.…”
Section: Discussionmentioning
confidence: 99%
“…One study has demonstrated that CASA can detect more cases with small volume disease than CA125, and that 50% of patients with microscopic disease are detected by CASA alone (473 ). Another study has shown that the prognostic value of postoperative serum CASA level is superior to CA125 and other parameters including residual disease, histological type, tumor grade, and the cisplatin-based chemotherapy (484 ).…”
Section: Prognosismentioning
confidence: 99%
“…Other investigators suggested progression criteria that were valid only during follow-up of patients where CA 125 concentrations had decreased to below the cut-off value after initial chemotherapy. According to these suggestions a positive CA 125 signal of progression was either based upon a single increment above the cut-off value (Niloff et al, 1986;van der Burg et al, 1990;Hising et al, 1991;Ward et al, 1993;Gard and Houghton, 1994), or upon an increase of concentrations to twice the upper limit of normal . Thus, several empirical criteria for CA 125 progression have been applied, but none have been precise enough to eliminate falsepositive results.…”
Section: Tablementioning
confidence: 99%